The problems of thinking about mind, body and experience - Тилеубаева, Меруерт Слямхановна; Масалимова, Алия Рмгазиновна; Kaufman, James C.; Fernandez, M.V.C. (ҚазҰУ Хабаршысы. Психология және әлеуметтану сериясы, 2017)
The psychology of thinking, the processes of interrelation of “mind” and “body” are investigated in this article. We try to reconcile the two available sources of information about mind and body. One source is science, which gives us insights into how brains work. Another source is introspection and opinions expressed by other people talking about their subjective experience, the method of observation. In the modern world remain topical issues of psychology of human thinking. Issues of external influence on the thinking reflected in numerous scientific papers where the object of the study was all the regularities of manifestation of the human psyche in various situations. It is human nature to think, because our world is not possible to imagine without science, and technology. And these phenomena are dangerous to the person, because every day we are confronted with the contradictions of reality. In connection with what the primary goal is a discovery of dependencies, regularities and mechanism, as well as their influence on problems of thinking, mind, body, and experience in the evolutionary process. We set the following tasks: – To study the processes of the psychology of thinking. – Is to consider the “nature” of education. – To study the processes of interrelation of “mind” and “body”. – To consider the mechanism and principles of evolution. – To identify the main problems in the psychology of thinking about mind, body and experience and make a generalization. – A study on the effect of thinking in the family. Since ancient times man was peculiar to know the world around him. Evolving as an individual, man gradually developed the thinking, the mind, the body and acquire experience. It is considered that thinking is mediocre (indirect) and generalized reflection of reality, a type of mental activity, namely, to know the essence of things and phenomena, natural connections and relations between them. Key words: body, experience, nature, mind.